2020
DOI: 10.1038/s41598-020-64365-x
|View full text |Cite|
|
Sign up to set email alerts
|

Different exercise training modalities produce similar endothelial function improvements in individuals with prehypertension or hypertension: a randomized clinical trial

Abstract: Endothelial dysfunction is a characteristic of systemic arterial hypertension (SAH) and an early marker of atherosclerosis. Aerobic exercise training (AT) improves endothelial function. However, the effects of resistance training (RT) and combined training (CT) on endothelial function remain controversial in individuals with SAH. We determined the effects of AT, RT, and CT on endothelial function and systolic (SBP)/diastolic blood pressure (DBP) in individuals with prehypertension or hypertension. Forty-two pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 38 publications
0
67
2
1
Order By: Relevance
“…The importance of physical training in promoting various health benefits, such as increased insulin sensitivity, diminished risk factors for metabolic syndrome, reduced blood pressure (preventing hypertension), and improved muscle metabolism and antioxidant capacity have been demonstrated [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Physical exercise promotes muscle mass and muscle functions by increasing muscle protein synthesis and stimulating mitochondrial biogenesis [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of physical training in promoting various health benefits, such as increased insulin sensitivity, diminished risk factors for metabolic syndrome, reduced blood pressure (preventing hypertension), and improved muscle metabolism and antioxidant capacity have been demonstrated [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Physical exercise promotes muscle mass and muscle functions by increasing muscle protein synthesis and stimulating mitochondrial biogenesis [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of these divergent findings with respect to the acute effect of exercise on FMD in healthy resistance-trained individuals, long-term resistance exercise is a well-established way to improve FMD in individuals at cardiovascular disease (CVD) risk, including those with prehypertension or hypertension [ 11 ] and overweight women [ 12 ]. Therefore, in no way should the practice of resistance exercise be seen as a health-damaging exercise model, but the acute effect of maximal resistance exercise on FMD could be taken into consideration during resistance exercise prescription for individuals that possess lower FMD values, such as those with CVD risk factors [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed improvements in FMD after eight weeks of an exercise training program without changes in cardiovascular risk factors, reinforcing the premise that hemodynamic stimuli caused by physical training play crucial roles in modulating endothelial function [ 6 ]. In light of this, Pedralli et al [ 11 ] recently reported that either resistance exercise or aerobic exercise, including the combination of aerobic and resistance exercise, for eight weeks improved FMD in individuals with prehypertension or hypertension. Similarly, Olson et al [ 12 ] also reported that 12 months of resistance training improved FMD in overweight women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In young prehypertensive patients, resistance training increases flow-mediated dilation and reduces blood pressure [ 279 ], as wells as improves resistance artery endothelial function and prooxidant/antioxidant balance [ 280 ]. In a recent randomized clinical trial, aerobic exercise training, resistance training, and combined training have also shown similar beneficial in improving endothelial function but impacts on ambulatory blood pressure appear to be variable in middle-aged and older individuals with prehypertension or hypertension [ 281 ].…”
Section: Physical Exercisementioning
confidence: 99%